Menganalisis Kemampuan Berpikir Kritis Peserta Didik pada Pembelajaran Biologi dalam Strategi Problem-Based Learning - Azla, Marisa; Efvita, Yuke; Laila, Rika Rahma (Multiverse: Open Multidisciplinary Journal, 2023)
The aim of this research was to analyze students' critical thinking abilities in biology learning process that used a problem-based learning strategy. This research used a quantitative approach, and research design was descriptive. The population consists of class X students at SMA N 2 Mandau. This research was conducted in August 2023. The total sample was 180 respondents. The instrument was questionnaires. The research results showed that an average percentage of 77.4% of respondents answered Yes, the meaning that respondents used their critical thinking skills in the biology learning process based on critical thinking indicators. Biology learning process at SMA N 2 Mandau showed the involvement of critical thinking skills using problem-based learning strategies. It was showed that students' critical thinking abilities was in the high category. Problem-based learning strategy can train the students to be more active in critical thinking.